Arkeologi Renjana: Membedah Identitas Bangsa melalui Wewangian Di Balik Tirai Aroma Karsa - Anak Agung Ngurah Bagus Janitra Dewanta; Lianda Dewi Sartika (Ruang Kata, 2026)
The dominance of synthetic aromatic products, which has led to the diffusion of cultural identity, provides the background for this study, which uses research-based literary works as a medium for reconstructing a detailed, emotional history. This study aims to map the traces of aromatic historical civilization in the Indonesian archipelago, as a cultural aspect documented in the book Behind the Curtain of Aroma Karsa by Dee Lestari, through a Sensory Archaeology approach. The study uses a descriptive qualitative method with library research and content analysis techniques. This study applies the Historicism Sensory History perspective, using the logical formulation I = (S × A) + C to measure the Cultural Identity variable (I) based on the correlation among Historical Data (S), Aroma Representation (A), and Social Context (C). Triangulation and classification techniques are used as data validation in this study, using the Weight of Evidence framework. The study identified 10 aroma categories, divided into three levels of identity. Sacred Aroma and Rare Botanicals were found to be the Fundamental elements with the highest scores, which represent transcendental spirituality and the biodiversity of the Indonesian archipelago. The other categories, namely the Aroma of Nobility, Territorial, Medical, Maritime, Mortality, Urban, and Archives, are classified as Strong, depicting social stratification and traces of maritime history in human sensory memory. Industrial Aroma is classified as Moderate, depicting the shift from philosophical values to economic commodities. The conclusion of this study confirms that aromas in fictional narratives function as artifacts and "living fossils," capable of preserving a nation's collective memory. The use of a sensory history approach has proven effective in reviving the often-overlooked history of ethnobotany and the archipelago's cultural identity.